2005
DOI: 10.12681/mms.195
|View full text |Cite
|
Sign up to set email alerts
|

Gametogenesis and spawning of Spirobranchus tetraceros (Polychaeta, Serpulidae) in Abu Kir Bay, Egypt

Abstract: The serpulid polychaete Spirobranchus tetraceros of Red Sea / Indo-pacific origin, recently has succeeded to establish a foothold in Alexandria Mediterranean waters. Worms were monthly scraped from submerged iron substrates at Abu Kir Bay during the period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
2
10
1
Order By: Relevance
“…We found five specimens of S. gardineri in this study, all of them associated with live Cyphastrea. The low abundance of S. tetraceros in this study is slightly surprising, having been reported to be a very abundant Lessepsian migrant in the Suez Canal and Mediterranean (Selim et al, 2005). However, records from the Red Sea never mention such a massive occurrence (e.g.…”
Section: Discussioncontrasting
confidence: 71%
“…We found five specimens of S. gardineri in this study, all of them associated with live Cyphastrea. The low abundance of S. tetraceros in this study is slightly surprising, having been reported to be a very abundant Lessepsian migrant in the Suez Canal and Mediterranean (Selim et al, 2005). However, records from the Red Sea never mention such a massive occurrence (e.g.…”
Section: Discussioncontrasting
confidence: 71%
“…gemineoa exhibited a cap-like appearance, which is similar to the acrosomal morphology observed in several other closely related polychaete species with ect-aquasperm (e.g. Hydroides dianthus , Serpula vermicularis , Vermiliopsis infundibulum [ 36 ] and Spirobranchus tetraceros [ 35 ]).…”
Section: Discussionsupporting
confidence: 73%
“…gemineoa and in some other polychaetes, such as Phragmatopoma lapidosa [ 21 ] and S . tetraceros [ 35 ]. The electron-dense fibrillary material, known as subacrosomal filaments, are presumed to be actin, which plays an important role in the acrosome reaction during fertilisation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its first Mediterranean record was from Lebanon in 1965 ( Laubier, 1966 ) as Spirobranchus giganteus coutierei Gravier, 1908 (which is now understood as a sub-species of Spirobranchus tetraceros ; E. Kupriyanova, 2017, personal communication), followed by Rhodes, Greece ( Dumont & Werger, 1989 ), Abu Kir Bay, the Egyptian Mediterranean ( Selim et al, 2005 ), and the Turkish Levantine Sea ( Çinar et al, 2006 ).…”
Section: New Nis Records: Notes On Individual Speciesmentioning
confidence: 99%